Lokakarya Kepala Sekolah dan Staf SMK Asji Tentang PPI - Paul Suparno (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
The purpose of this workshop was to help ASJI’s SMK principals and curriculum staff better understand the Ignatian Pedagogical Paradigm (Paradigma Pedagogi Ignatian -- PPI). The SMK principals and staff were aware that they did not understand enough what PPI was and how to apply PPI in the context of Vocational High Schools (Sekolah Menengah Kejuruan -- SMK). So they wanted to know better and learned more about the PPI spirit, values, and dynamics.To help those principals and staff’s needs, ASJI provided a workshop on PPI. A lecturer from Sanata Dharma University was invited to guide the workshop as an instructor. During the workshop, the participants discussed PPI and planned how to apply and improve PPI in their own schools. The result was that every school made one program (RPP) to implement PPI in their schools.